Analisis Asam Askobat dalam Sediaan Tablet A dan Minuman Suplemen B dengan Metode Spektrofotometri UV-Vis Genesis 10s - Purba, Hermawan; Faneca, Egia; Anggreni, Wulan (Program Studi S1 Farmasi, STIKES Senior, Medan, 2025)
Vitamin C is one of the nutrients that acts as an antioxidant and is effective in fighting free radicals that can potentially damage cells or tissues, including protecting the lens of the eye from oxidative damage caused by radiation. Additionally, Vitamin C can also help reduce the risk of cancer and prevent damage caused by free radicals that can trigger cancer development. The purpose of this research is to determine the vitamin C content in tablet A and drink B using the UV-Vis spectrophotometry method with the Genesis 10S. This study is descriptive in nature, focusing on the determination of vitamin C levels in tablet A and drink B using the UV-Vis spectrophotometry method with the Genesis 10S. To prepare a concentration series of 2; 4; 6; 8; 10 ppm, pipette from the stock solution of Chloramphenicol at 1000 mg/L. Each sample is placed into a 10 ml volumetric flask and diluted with distilled water up to the mark.Then, an examination was conducted on each concentration using UV-Vis spectrophotometry. After the curve appeared, the calibration curve was obtained by examining the relationship between concentration (X) and the area under the chromatogram (Y) and determining its regression equation (y= ax + b). The results of the analysis of ascorbic acid in tablet preparation A and drink B using the UV-Vis Genesis 10s spectrophotometry method yielded a linear equation for the calibration curve between absorbance and the concentration of the standard solution, resulting in the equation Y = 0.0395x- 0.0443 with an r² value of 0.9853.